Molecular phylogenetics of the Ophiocordyceps sinensis-species complex lineage (Ascomycota, Hypocreales), with the discovery of new species and predictions of species distribution - Yongdong Dai; Siqi Chen; Yuanbing Wang; Yao Wang; Zhuliang Yang; Hong Yu (IMA Fungus)
Abstract Ophiocordyceps sinensis is a famous traditional Chinese medicine adapted to the alpine environment of the Qinghai-Tibet Plateau and adjacent regions. Clarification of the species diversity of Ophiocordyceps sinensis and its relatives could expand the traditional medicinal resources and provide insights into the speciation and adaptation. The study is prompted by the discovery of a new species, O. megala, described here from a biodiversity hotspot in the Hengduan Mountains, China. Combined morphological, ecological, and phylogenetic evidence supports its distinctiveness from O. sinensis, O. xuefengensis, and O. macroacicularis. Additionally, based on the phylogenetic construction of Ophiocordyceps, a special clade was focused phylogenetically on the more closely related O. sinensis complex, which was defined as the O. sinensis- species complex lineage. A total of 10 species were currently confirmed in this lineage. We made a comprehensive comparison of the sexual/asexual morphological structures among this species complex, distinguishing their common and distinctive features. Furthermore, using the method of species distribution modelling, we studied the species ocurrences in relation to climatic, edaphic, and altitudinal variables for the eight species in the O. sinensis-species complex, and determined that their potential distribution could extend from the southeastern Qinghai-Tibet Plateau to the Xuefeng Mountains without isolating barrier. Thus, the biodiversity corridor hypothesis was proposed around the O. sinensis-species complex. Our study highlights the phylogeny, species diversity, and suitable distribution of the O. sinensis-species complex lineage, which should have a positive implication for the resource discovery and adaptive evolution of this unique and valuable group.